Implementasi Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) Penentuan Penerimaan Bantuan Siswa Miskin (BSM) - Adliana Iswani; Bachtiar Efendi; Chitra Latiffani (LPPM STMIK Royal Kisaran, 2021)
Abstract: The decision support system using the Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) method is a system for making decisions with many criteria. One of the implementations is for poor student assistance recipients. There are many students who apply, so there is a problem in SMK Negeri 1 Fifty that it is difficult to select the file for poor student aid recipients who will get the assistance. Based on these problems, a decision support system is needed to welcome recipients of poor student assistance who really deserve to get assistance. The programming language used is Visual Basic Net 2010 and MySQL database as well as the Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) method. So the results obtained are a decision support system using the MOORA method can make decisions from a decision that is through the ranking of students who are eligible to get poor student assistance. Keywords: Decision Support System, Poor Student Assistance, MOORA Abstrak: Sistem pendukung keputusam dengan menggunakan metode Multi-Objective Opti-mization On The Basis Of Ratio Analysis (MOORA) merupakan suatu sistem dalam pengambilan keputusan banyak nya kriteria. Salah satu implementasinya yaitu untuk penentuan penerima bantuan siswa miskin. Ada banyak nya siswa yang mengajukan berkas, sehingga muncul permasalahan di SMK Negeri 1 Lima Puluh sulitnya menyeleksi berkas penerima bantuan siswa miskin yang akan mendapatkan bantuan tersebut. Berdasarkan permasalahan tersebut maka dibutuhkan sistem pendukung keputusan untuk penentuan penerima bantuan siswa miskin yang benar – benar layak untuk mendapatkan bantuan. Bahasa pemrograman yang digunakan adalah Visual Basic Net 2010 dan database MySQL dan dengan metode Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA). Maka hasil yang didapat adalah sistem pendukung keputusam dengan menggunakan perhitungan metode MOORA dapat mempercepat dalam pengambilan suatu keputusan yaitu melalui ranking siswa yang layak untuk mendapatkan bantuan siswa miskin Kata kunci: Sistem Pendukung Keputusan, Bantuan Siswa Miskin, MOORA